2006
DOI: 10.1007/s10620-006-3078-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Esophageal Varice Eradication on Portal Hypertensive Gastropathy and Fundal Varices: A Retrospective and Comparative Study

Abstract: Esophageal varice eradication results in gastric hemodynamic changes. The aim of this study was to detect the influence of variceal eradication on portal hypertensive gastropathy (PHG) and fundal varices and to compare the results of two therapeutic methods (endoscopic variceal ligation and endoscopic sclerotherapy). A total of 114 consecutive patients with cirrhosis and portal hypertension who underwent elective endoscopic variceal ligation (EVL) (85 patients) or endoscopic sclerotherapy (EST) (29 patients) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…14,20 It is interesting to note that in two-thirds of our patients, fundal varices disappeared after esophageal variceal eradication. Gastric varices, particularly those of GOV1 type, are often an extension of esophageal varices and hence are obliterated by injection of sclerosant into the latter.…”
Section: Discussionmentioning
confidence: 64%
“…14,20 It is interesting to note that in two-thirds of our patients, fundal varices disappeared after esophageal variceal eradication. Gastric varices, particularly those of GOV1 type, are often an extension of esophageal varices and hence are obliterated by injection of sclerosant into the latter.…”
Section: Discussionmentioning
confidence: 64%
“…Sarin et al found that among 88 patients with PHG, 74% developed this condition after variceal eradication [29]. The severity of the PHG also seems to increase after endoscopic variceal treatment, either by sclerotherapy or by band ligation [31]. On the other hand, it seems that esophageal variceal band ligation does not affect the incidence of anorectal varices or PHC [32].…”
Section: Discussionmentioning
confidence: 99%
“…2 Indeed, we recommend caution in performing band ligation in patients with smaller varices, as highlighted by a recent study. 3 This demonstrated a high incidence of banding-related bleeding when patients with smaller varices were included. In our study, none of the patients had red signs at endoscopy, but it is not clear whether patients without red signs should be excluded from band ligation.…”
Section: Is Endoscopic Band Ligation Necessary For Primary Prophylaximentioning
confidence: 93%
“…Recently, we have reported that esophageal variceal eradication with either band ligation or sclerotherapy increased both the incidence and the severity of portal hypertensive gastropathy and gastric varice formation. 3 We wonder about the number of patients who developed gastric varices and portal hypertensive gastropathy in each group in the study performed by Tripathi et al This will help us to have some information whether gastric varix formation and development of portal hypertensive gastropathy occur as complications of endoscopic variceal treatment or as a natural course of the underlying portal hypertension and cirrhosis. Reply:…”
mentioning
confidence: 99%